STATEMENTS ACCOUNTING FOR BALANCE SHEET CHANGES. - Myer, John N. (The Accounting Review, 1944)
Examination of changes in the position of accounts listed in successive balance sheets of a business is a useful analytical procedure. There are two kinds of statements for this purpose that may be derived from financial statements. Statement accounting for variation in net worth is a form of comparative balance sheet showing changes in account balances between balance-sheet dates is shown in the article. Changes are classified according to their effect on net worth, increases in assets and decreases in liabilities and reserves cause an increase in net worth, while decreases in assets and increases in liabilities and reserves result in a decrease in net worth. The change in net worth is the difference between these increases and decreases and this change is accounted for by the total of changes in the items composing net worth, in this instance, capital stock and surplus. This statement has been named by the writer the statement accounting for variation in net worth. The second kind of statements is statement accounting for variation in working capital. The vital activities of a business, such as the acquisition of capital and the liquidation of indebtedness, the purchase of equipment and merchandise, and the appearance of revenues and expenses, are reflected in the current asset and current liability accounts.